Pelatihan UMKM Naik Kelas: Studi Kasus UMKM Desa Sirnajaya, Kecamatan Serang Baru, Kabupaten Bekasi - Naftalie, Bellatasya; Asral Asral; Ayu Kartika Agustin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The MSMEs gradetraining in Sirnajaya Village, Serang Baru District, Bekasi Regency, aims to increase the capacity of Micro, Small, and Medium Enterprises (MSMEs) to utilize digital technology for marketing. Given MSMEs significant contribution to the Indonesian economy, this training focuses on an introduction to digital marketing, e-commerce, and financial management. Through a participatory approach, needs analysis, and hands-on training implementation, participants are expected to overcome obstacles in product marketing. The training results demonstrate an increase in digital understanding and skills, which are expected to expand markets and increase MSMEs competitiveness in the digital era.